Writing on the tablet of the heart : origins of Scripture and literature - Carr, David McLain, 1961- (OUP E-Books., 2005)
This book explores a new model for the production, revision, and reception of Biblical texts as Scripture. Building on recent studies of the oral/written interface in medieval, Greco-Roman and ancinet Near Eastern contexts, David Carr argues that in ancient Israel Biblical texts and other texts emerged as a support for an educational process in which written and oral dimensions were integrally intertwined. The point was not incising and reading texts on parchment or papyrus. The point was to enculturate ancient Israelites - particularly Israelite elites - by training them to memorize and recite a wide range of traditional literature that was seen as the cultural bedorck of the people: narrative, prophecy, prayer, and wisdom.